2008
DOI: 10.2193/2006-420
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Road Crossings on Stream and Streamside Salamanders

Abstract: Salamanders are important members of faunal communities in Appalachian Mountain (USA) streams, and the use of salamanders as bioindicators is increasing. Roads are a part of the modern landscape, but effects of roads on stream and streamside salamander diversity and abundance is not clear. We sampled streams in central West Virginia, USA, using quadrats placed along transects in the flowing channel, dry channel, and stream bank to assess salamander diversity, richness, and abundance during 2004. We used Akaike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 50 publications
2
30
0
1
Order By: Relevance
“…Microhabitat features such as soil moisture and cover object area tend to decrease in the proximity of roads [52]. In addition, roads can reduce edge permeability due to factors such as behavioral aversion and increased mortality from road crossing [147,153]. Gibbs [147] found that roads appeared to be a significant anthropogenic landscape component restricting salamander movement.…”
Section: Roadsmentioning
confidence: 99%
See 2 more Smart Citations
“…Microhabitat features such as soil moisture and cover object area tend to decrease in the proximity of roads [52]. In addition, roads can reduce edge permeability due to factors such as behavioral aversion and increased mortality from road crossing [147,153]. Gibbs [147] found that roads appeared to be a significant anthropogenic landscape component restricting salamander movement.…”
Section: Roadsmentioning
confidence: 99%
“…Gibbs [147] found that roads appeared to be a significant anthropogenic landscape component restricting salamander movement. Multiple studies have found that roads negatively affect salamander abundance [52,147,152,153]. For instance, red-backed salamanders are significantly less abundant near gravel road edges, perhaps due to corresponding lower soil moisture [52].…”
Section: Roadsmentioning
confidence: 99%
See 1 more Smart Citation
“…Salamanders have received little consideration for passage through culverts [2], [3]. Most studies focus on the passage of fish, including the development of computer software to analyze culvert passage issues [2], [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Culvert hang and slope as described above is also a major factor contributing to passage issues. Newly constructed roads that cross streams need to be built in a manner to not restrict any form of aquatic life movement, not just fish [3].…”
Section: Introductionmentioning
confidence: 99%